PERANCANGAN SISTEM MANAJEMEN GUDANG MATERIAL RESIN DI PT. II - Ossa Sutaarga; Dian Friana Hidayat (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2018)
Management system at Resin warehouse in PT II still has many problems within. Improvement in management system needs to be done to overcome that problem. The difference between actual product’s amounts and the record, unscheduled planning production, and unorganized warehouse layout are the problem of this company. Improvement for the record of actual product inside warehouse isn’t to match the record of administration record. This process would be necessary to reduce the gap in stock opname process. MPS can be use to determine the ideal time and the ideal amount of total production for company, so that the inventory cost could be reduced. And then maximal capacity at Resin warehouse increase to 270% and increase the area until 26% squaremeter. Inventory turn over in the warehouse became better. The day sale in inventory was reduced from 17 days to 16 days.